Strategi Guru PAI dalam Menerapkan Konsep Merdeka Belajar di SMP Swasta Sabilina Tembung - Bako, Nurhayati; Siregar, Ramadhani; Hasanah, Uswatun (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to describe and analyze the strategies of Islamic Education teachers in implementing the concept of Independent Learning at Sabilina Tembung Private Junior High School. The three main aspects studied are the planning stage, the implementation stage, and the evaluation stage carried out by Islamic Education teachers in implementing the concept of Independent Learning at Sabilina Tembung Private Junior High School. This research is a qualitative study using field observation techniques, interviews, and documentation. The results of this research show that the strategies used by Islamic Education teachers at Sabilina Tembung Private Junior High School in the planning, implementation, and evaluation stages are: 1) Developing and creating learning tools by applying Independent Learning, namely the Learning Objective Flow (ATP), 2) Implementation of the Independent Learning Curriculum, where the methods and strategies used by teachers should be student-centered, 3) Evaluation of Islamic Education teachers in implementing the Independent Learning Curriculum at Sabilina Tembung Private Junior High School.